World Internet Development Report 2017 Translated by Peng Ping - Chinese Academy of Cyberspace Studies; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
An important outcome of the Fourth World Internet Conference, this book provides a comprehensive account of the status quo and trends in global Internet development. Covering network infrastructure, information technology, digital economy, e-governance, cyber security, and international cyberspace governance, it presents the Global Internet Development Index System to assess the Internet development of various major countries and emerging economies. .
Contents -- Overview -- History of the World Internet -- Development of the World$1 (Bs Information Infrastructure -- Development of the World$1 (Bs Network Information Technology -- The World$1 (Bs Cyber Security -- Development of the World$1 (Bs Digital Economy -- World$1 (Bs E-governance Development -- Development of the World$1 (Bs Internet Media -- Global Cyberspace Governance -- Afterword.s
Keywords: Telecommunication; Application software; Signal processing; Industrial Management; Technology; History; Communications Engineering, Networks; Computer and Information Systems Applications; Signal, Speech and Image Processing .; Industrial Management; History of Technology